Implementation of Oil Spill Management through Regional Regulations in Sustainable Coastal Environment Management in Bintan - Hamzah, A Hadian Pratama; Suryani, Cicik; Nurhasanah, Nurhasanah; Harijati, Sri (Faculty of Law, Universitas Pekalongan, 2024)
Indonesia is called a maritime country with potential in marine resources, for example capture fisheries and oil and gas deposits at the bottom of the ocean. Apart from its natural resources, Indonesia has sovereignty over territorial seas which include; inland waters, archipelago waters, and territorial seas. This paper focuses on analyzing how regional regulations are implemented in managing oil spills in the coastal environment of Bintan Regency, Riau Islands. This research uses a type of juridical-normative research, also known as doctrinal, with the object or target of the research being statutory regulations and other legal materials. The results obtained show that regional regulations are not yet optimal in managing oil spill issues. In this article there are also good recommendations for stakeholders from both regional and central levels.